2018
DOI: 10.1558/sols.33280
|View full text |Cite
|
Sign up to set email alerts
|

Italian-dialect code-switching in Sicilian youngsters

Abstract: The paper deals with the role of dialect among young Sicilian speakers. After a brief overview of the conditions of local dialects in Western Europe, I will discuss the main results of research carried out by means of different methodological approaches and types of data: (i) self-evaluative data elicited through questionnaire; (ii) a corpus of spontaneous spoken language; (iii) a written corpus of e-mails, text messages, posts in social networks, etc. The study shows a strong functional specialization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Moreover, the view that the Sicilian dialect acquires an important communicative function within the repertoire of young speakers, as promoted for instance by current sociolinguistic investigations of codeswitching (e.g. Alfonzetti, 2017) is therefore confirmed, on a different descriptive scale, by our data. This also open the question on how properly define vernacular, regional and supra-regional forms, in terms of quantity and quality of phonetic features.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, the view that the Sicilian dialect acquires an important communicative function within the repertoire of young speakers, as promoted for instance by current sociolinguistic investigations of codeswitching (e.g. Alfonzetti, 2017) is therefore confirmed, on a different descriptive scale, by our data. This also open the question on how properly define vernacular, regional and supra-regional forms, in terms of quantity and quality of phonetic features.…”
Section: Discussionsupporting
confidence: 84%
“…An additional character of the standard/dialect dynamics in Sicilian territories, that is worth recalling here, is that the dialect loses ground as language of primary socialization, but at the same time, most of the youngest speakers start to use the dialect as an L2, particularly within the peer group (Alfonzetti, 2014(Alfonzetti, , 2017Scaglione, 2016). Many authors suggest that the relationship between young speakers and the dialect is ambiguous.…”
Section: Introductionmentioning
confidence: 96%
“…The strategies identified in the multimodal task artefacts speak to the linguistic and cultural diversity present in the Italian context, with heritage language inclusion representing the most commonly emerging strategy. By contrast, the least commonly used strategy of including regional diversity may indicate a need to continue to promote dialectal language varieties, which are frequently stigmatised in Italy and other European nations (e.g., Alfonzetti, 2017) and represent a key priority for human rights in language education. On the other hand, the frequently used strategy of including non-heritage languages, such as other languages studied at school, destabilises concerns that a 'multicultural' class is needed in order to practise plurilingual pedagogies, and thereby advances further avenues for promoting language rights in class.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to addressing different audiences, some researchers like Gumperz (1982) suggested that switching languages is important in order to specify the addressees and to convey messages when they are targeted at different listeners or recipients, to facilitate easy understanding. For example, research by Alfonzetti (1998) on Italian-dialect switching suggested that CS can be used for conversational analysis of communicative competence and that CS occurring naturally among bilinguals is a communicative approach employed specifically for the purposes of the speaker. It can be considered as a cue for the recipient to interpret the given message a certain way.…”
Section: Motivations and Functions Of Csmentioning
confidence: 99%
“…Researchers have argued that CS is a self-repair tool (Auer, 1998;Wei & Milory, 1995;Alfonzetti, 1998;Matras 2009). In face-to-face interaction, it is often used with other repair practices like those that Poplack and Sankoff (1988) called "flagging" hesitation pauses, vowel stretching and other paralinguistic characters such as body gestures.…”
Section: Cs In Dmc Vs Offline Communicationmentioning
confidence: 99%